Associations of perceived stress with depression in medical students: the mediating role of rumination and the moderating role of emotional intelligence - Hong, Youjuan; Luo, Lina; Li, Zixuan; Wu, Siyu; Bao, Xiaofan (Frontiers in Psychology, 2025)
BackgroundMedical students have become a group with a high prevalence of depression and are particularly vulnerable to it. Recognizing the factors affecting depression among medical students is crucial. This study was aimed at exploring the effects of perceived stress on medical students’ depression under the mediating role of the rumination and the moderating role of the emotional intelligence.MethodsA survey was conducted with 648 medical students in XX Province, XX (blind review). Participants provided responses to measures of perceived stress, rumination, emotional intelligence, and depression. Data analysis was performed in SPSS version 26 and the SPSS PROCESS Macro.ResultsThe results revealed significant positive associations between perceived stress (r = 0.63, p < 0.01) and rumination (r = 0.59, p < 0.01) with depression. Rumination plays a mediating role between perceived stress and depression, with the mediation effect accounting for 31.67% (SE = 0.10, 95% CI = 0.15, 0.26). Furthermore, emotional intelligence significantly moderated the direct effect (moderated mediation = −0.01, SE = 0.01, 95% CI = −0.01, −0.00).ConclusionRumination serves as a mediator in the relationship between perceived stress and depression, while emotional intelligence significantly moderates the impact of perceived stress on depression.